The Influence Of Mental Health, Workload Pressure, And Job Stress On Employee Performance Quality At Disnakertrans Tulungagung - Amanda, Shella Amalia; Laksono , Sonny Subroto Maheri; Nadhiroh, Umi (CV. Lenggogeni Data Publishing, 2023)
This research is motivated by the importance of performance quality in a company, as employees are the driving force behind the company's success. In order to achieve maximum performance quality, it is influenced by several factors that make the company's vision and mission easier to achieve with good coordination. This study connects independent variables including mental health, workload pressure, and job stress with the dependent variable, which is employee performance quality. The method used in this research is quantitative analysis. The quantitative data collection technique employed involves distributing questionnaires and conducting interviews with 47 employees of Disnakertrans Tulungagung. Meanwhile, for quantitative data analysis in this study, validity tests, reliability tests, normality tests, classic assumption tests (multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression analysis, hypothesis testing, and determination coefficient (R2) are utilized.The results of this research indicate that: 1) There is a positive and significant influence of mental health on employee performance quality. 2) There is a negative and significant influence of workload pressure on employee performance quality. 3) There is a negative and significant influence of job stress on employee performance quality. 4) Collectively, mental health, workload pressure, and job stress variables have a positive and significant influence on employee performance quality (Y) at Disnakertrans Tulungagung.